Encyclopedia of Science & Technology (8 GEO-HYS) (ĐĨA CD) - Hill McGraw (MC Graw Hill, 2007)
The Encyclopedia of Science & Technology present pertinent information in every filed of modern science and technology. The 7100 articles are arranged alphabetically in the 19 text volumes. The range of article titles included in each volume is indicated on the spine and front cover. Thus the reader may quickly locate by its title. The 20th volume contains the indexes and ancillary. This volume 8 contains articles with titles starting with "GEO" up "HYS"